2017
DOI: 10.1142/s2010135x17500096
|View full text |Cite
|
Sign up to set email alerts
|

All-dielectric metamaterial frequency selective surface based on spatial arrangement ceramic resonators

Abstract: In this paper, we demonstrate a method of designing all-dielectric metamaterial frequency selective surface (FSS) with ceramic resonators in spatial arrangement. Compared with the traditional way, spatial arrangement provides a flexible way to handle the permutation and combination of different ceramic resonators. With this method, the resonance response can be adjusted easily to achieve pass/stop band effects. As an example, a stop band spatial arrangement all-dielectric metamaterial FSS is designed. Its work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Dielectric resonator theory provides a description of the variational resonant modes, especially for dielectric resonators with complex shapes [173,174]. To select suitable relative permittivity, geometrical shapes, and sizes of dielectric blocks, various resonance modes can be stimulated at required frequencies [175,176]. Resonance enhanced displacement current are usually found in high permittivity dielectric resonators, when the electric size of the resonator is correlated with the wavelength of the incident electromagnetic waves.…”
Section: Metamaterial/metasurface Design Using High Permittivity Ferr...mentioning
confidence: 99%
“…Dielectric resonator theory provides a description of the variational resonant modes, especially for dielectric resonators with complex shapes [173,174]. To select suitable relative permittivity, geometrical shapes, and sizes of dielectric blocks, various resonance modes can be stimulated at required frequencies [175,176]. Resonance enhanced displacement current are usually found in high permittivity dielectric resonators, when the electric size of the resonator is correlated with the wavelength of the incident electromagnetic waves.…”
Section: Metamaterial/metasurface Design Using High Permittivity Ferr...mentioning
confidence: 99%
“…With the same idea of building blocks, different unit cells are proposed. [59][60][61] The combination of different modes can inspire various resonant behaviors to introduce different impedance characteristics.…”
Section: Dielectric Particle-based Adm-fssmentioning
confidence: 99%
“…into a background matrix on the metallic ground plane obtaining dual-band metamaterial absorber. Li et al [23] made use of complex all-dielectric E-shaped structure attaining broadband absorber. Huang et al [24] demonstrated the magnetically-biased frequency-tunable absorption by integrating a ferrite as the substrate or superstrate into the conventional planar MMA, not directly using ferrite particles as resonator.…”
Section: Introductionmentioning
confidence: 99%